Rearing the larval stages of Distoleon tetragrammicus (Fabricius, 1798) (Neuroptera: Myrmeleontidae) from egg to adult, with notes on their behaviour - Satar Ali̇; Suludere Zeki̇ye; Canbulat, Savaş; Özbay Cengi̇zhan (Zootaxa, 2006)
Eggs of the ant-lion Distoleon tetragrammicus (Fabricius, 1798) were obtained from gravid females for the first time. Larvae were reared to the adult stage from eggs. The eggs and the different parts of the larva such as head, mandibles and antennae, are described and illustrated and larval behavior in each stage was monitored.